2018
DOI: 10.1186/s13227-017-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene’s role in an ancient mechanism: secreted Frizzled-related protein 1 is a critical component in the anterior–posterior Wnt signaling network that governs the establishment of the anterior neuroectoderm in sea urchin embryos

Abstract: The anterior neuroectoderm (ANE) in many deuterostome embryos (echinoderms, hemichordates, urochordates, cephalochordates, and vertebrates) is progressively restricted along the anterior–posterior axis to a domain around the anterior pole. In the sea urchin embryo, three integrated Wnt signaling branches (Wnt/β-catenin, Wnt/JNK, and Wnt/PKC) govern this progressive restriction process, which begins around the 32- to 60-cell stage and terminates by the early gastrula stage. We previously have established that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…Strikingly, analysis of spatial expression of ANE markers in Axin-overexpressing embryos showed that ANE markers were broadly expressed throughout the anteriorized embryos (Range et al, 2013). Since Axin is a strong negative regulator of cWnt signaling, this result was consistent with a body of evidence that cWnt pathway-dependent signals from posterior cells restrict the ANE domain to the anterior pole of the embryo (Range et al, 2013;Range, 2014;Range, 2018;). However, the Range et al (2013) study did not carry out any molecular analyses on the effects of Axin overexpression on cWnt activation and endomesoderm specification and hence, we examined these processes in the Axin-mediated anteriorized embryos.…”
Section: Axin Regulates Cwnt Signaling and Normal Endomesoderm Specifsupporting
confidence: 75%
See 1 more Smart Citation
“…Strikingly, analysis of spatial expression of ANE markers in Axin-overexpressing embryos showed that ANE markers were broadly expressed throughout the anteriorized embryos (Range et al, 2013). Since Axin is a strong negative regulator of cWnt signaling, this result was consistent with a body of evidence that cWnt pathway-dependent signals from posterior cells restrict the ANE domain to the anterior pole of the embryo (Range et al, 2013;Range, 2014;Range, 2018;). However, the Range et al (2013) study did not carry out any molecular analyses on the effects of Axin overexpression on cWnt activation and endomesoderm specification and hence, we examined these processes in the Axin-mediated anteriorized embryos.…”
Section: Axin Regulates Cwnt Signaling and Normal Endomesoderm Specifsupporting
confidence: 75%
“…In addition to the role of cWnt signaling in specifying endomesoderm in vegetal cells, there is very good evidence that cWnt-dependent signaling from these cells initiates a signaling cascade that restricts anterior neural ectoderm (ANE) cell fates to the most anterior end of the embryo (Range, 2014;Range et al, 2013;Yaguchi et al, 2008). Several studies have shown that secreted Wnt inhibitors expressed in embryos around the time of gastrulation protect the ANE territory from posterior Wnt signaling similar to what has been shown in other bilaterian taxa (Khadka et al, 2018;Range, 2014;Range et al, 2013;Range and Wei, 2016). While many aspects of the ontogeny of cWnt-mediated AP axis patterning in the sea urchin embryo are similar to what is observed in other embryos it is not clear if there is a repression of cWnt signaling in the early embryo analogous to what has been seen in vertebrates and Tribolium.…”
Section: Introductionmentioning
confidence: 78%
“…It might be better to suppose that the spatial expression of foxQ2 at the later stage is likely maintained by the combination of global activators including Meis and unknown factors expressed specifically in the anterior neuroectoderm (and possibly a global repressor for foxQ2b ), that is, its expression is not caused by global activation and repression in the nonanterior region. A previous study examining S. purpuratus has reported that sequential Wnt signaling restricts foxQ2 expression into the future anterior neuroectoderm (Khadka, Martínez‐Bartolomé, Burr, & Range, ; Range et al, ). In the later phase of foxQ2 expression, Fzl5/8‐JNK noncanonical Wnt signaling represses foxQ2 expression in the nonanterior neuroectoderm.…”
Section: Discussionmentioning
confidence: 99%
“…The sFRPs play an important role in blocking Wnt signaling activity during embryogenesis. Indeed, the antagonizing activity of sFRP1 on Wnt1/Wnt8–Fzl5/8–JNK signaling was necessary for anterior neuroectoderm formation in sea urchin embryos (Khadka, Martínez‐Bartolomé, Burr, & Range, ). sFRP was previously reported to have an inhibitory effect on cancer cell growth in colorectal cancer and breast cancer cells through blocking the Wnt signaling pathway (Lavergne et al, ).…”
Section: Proteins Interacting With Unsaturated Fatty Acylated Wntsmentioning
confidence: 99%